Diclofenac for prophylaxis of heterotopic ossification after hip arthroplasty: a systematic review. Issue 2 (March 2022) - Haffer, Henryk; Müller, Michael; Ascherl, Rudolf; Perka, Carsten; Winkler, Tobias
Background: Heterotopic ossification (HO) is defined as the formation of lamellar bone in extraskeletal soft tissues. HO can be a severe complication after hip arthroplasty but can possibly be prevented by postoperative treatment with non-steroidal anti-inflammatory drugs (NSAIDs) or radiotherapy. Diclofenac is 1 of the most used drugs in HO prophylaxis because it is effective and long established. However, there is still no uniform therapy regimen in terms of duration, dose and side effect profile regarding the application of diclofenac in HO prevention. We have, therefore, conducted the first systematic review investigating diclofenac for HO prophylaxis after hip arthroplasty. The aim of this study is to assess the efficacy, dose and duration of diclofenac therapy in preventing HO after total hip arthroplasty (THA). Methods: According to the PRISMA Guidelines we performed a systematic literature search in EMBASE via Ovid, in MEDLINE via PubMed and in the Cochrane Library addressing all studies in English and German regarding the prophylaxis of HO with diclofenac after THA. We identified 731 potential studies and included 6 randomised controlled trials with 957 patients. Results: The studies were heterogeneous with regard to duration of therapy, dose, comparative group and follow-up period. The therapy duration ranged from 9 to 42 days, the applied diclofenac doses ranged from 75 mg to 150 mg daily. Patients treated with diclofenac showed a significant reduction in the total incidence of HO regarding to the Brooker Classification compared to placebo and no clinically relevant ossifications occured (Brooker III and IV). Conclusions: Diclofenac is efficacious in the prevention of HO and can be used routinely after THA. The existing data indicates that a minimum dose of 75 mg diclofenac per day started on the first postoperative day for a minimum of 9 days is needed to prevent HO with an acceptable incidence of side effects, such as gastrointestinal symptoms.